An aspect-oriented framework for orthogonal persistence - Pereira, Rui Humberto (2010)
The life cycle of software applications in general is very short and with extreme volatile requirements. Within these conditions programmers need development tools and techniques with an extreme level of productivity. We consider the code reuse as the most prominent approach to solve that problem. Our proposal uses the advantages provided by the Aspect-Oriented Programming in order to build a reusable framework capable to turn both programmer and application oblivious as far as data persistence is concerned, thus avoiding the need to write any line of code about that concern. Besides the benefits to productivity, the software quality increases. This paper describes the actual state of the art, identifying the main challenge to build a complete and reusable framework for Orthogonal Persistence in concurrent environments with support for transactions. The present work also includes a successfully developed prototype of that framework, capable of freeing the programmer of implementing any read or write data operations. This prototype is supported by an object oriented database and, in the future, will also use a relational database and have support for transactions.